Epidural abscess - an anesthetic complication - Carvalho, Inês; Tomé, Sara; Osório, Joana; Dinis, Isabel (Journal of the Portuguese Society of Anesthesiology, 2015)
Epidural abscess is an important infection which can expand and compress the central nervous system, causing severe symptoms and sequelae. This case is a description of a post-operative complication that occurred after a total knee arthroplasty. Although epidural abscess is an uncommon disease, there is some evidence that the incidence may have increased over the last 30 years, related to the improvement in diagnosis by the use of magnetic resonance imaging for spinal evaluation and also to the aging of the population and increases in the number of patients undergoing regional anaesthesia procedures. Thinking of epidural abscess is the key to diagnosis, especially whenever an immunocompromised patient was submitted to surgery under regional anesthesia technique. If the appropriate window of opportunity is missed, there can be compromise to the full recovery of the patients and the development of neurological deficits